Controlling matrix converter in flywheel energy storage system using AFPM by processor-in-the-loop method - Nguyen Hung Do; Sy Manh Ho; Quoc Tuan Le; Tung Hoang; Trong Minh Tran; Phuong Vu (Bulletin of Electrical Engineering and Informatics, 2022)
Flywheel energy storage systems are considered as the grid integration of renewable energy sources due to their inherent advantages such as fast response, long cycle life and flexibility in providing auxiliary services to the grid, such as frequency regulation, and voltage support. The article focuses on the design of the controller, then conducts processor-in-the-loop (PIL) simulation of the dynamics part using the axial flux permanent magnet (AFPM) motor with the matrix converter on MATLAB/Simulink combined with the controller on the TMS32F28377S microcontroller card of Texas Instruments to evaluate the efficiency of the energy storage system.